Development of Social Work Education in Nepal: A Historical Review (Siddhajyoti Interdisciplinary Journal, 2024)
Social work is not a new discipline in Nepal. However, it is slowly expanding professionally and currently faces various challenges. Including need to rely on modern techniques, cultural distancing from the environment and strategies because there is not a professional social work model in Nepal. In addition, difficulties include a lack of training, guidelines, and instruction at the governmental level; absence of functioning associated social organizations’ ethics, and accountability on the part of social workers. This study seeks to address issues impeding professionalism to protect service users. The search engines Google, Google Scholar, Google Book, ProQuest, and Eric, etc. were used in this study. Two primary themes were studied: the challenges and implications of social work education in Nepal. To discuss findings, content analysis of the themes was employed. This study finds that social work practice needs to be properly regulated and accredited. The social worker should promote social work practice and instruction. Social workers ought to be recognized by the government to increase funding in the field. The Nepalese social work model can be developed with the help of practitioners and even service users. The vision for Nepalese social work should be to get the profession recognized and strengthen the association of social work.